Sophistication of Information Technology, Effectiveness of Accounting Information Systems, Management Participation and Employee Performance - Amelia Larissa; Gede Juliarsa (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
This study aims to provide empirical evidence regarding the influence of information technology sophistication, effectiveness of accounting information systems, and management participation, using qualitative data, by distributing questionnaires to employees who meet the specified criteria. The population in this study were all employees of PT Mitrajaya Sumber Abadi, with a sample of 40 using purposive sampling technique. This research was tested with multiple linear analysis. The variables of information technology sophistication, effectiveness of accounting information systems, and management participation have a positive and significant effect on employee performance at PT. Eternal Success Mitrajaya.